Development, Characterization, and Exploitation in Food Systems of Functional Ingredients Obtained from Artichoke By-Products Phenolic Extracts - Francesco Iervese; Arianna Paluzzi; Michela Cannas; Giulia D’Alessio; Antonio Piga; Carla Di Mattia (Molecules)
The study aimed to assess the technological properties of six ethanolic phenolic-rich extracts derived from artichoke bracts, stems, and leaves using different extraction methods (maceration and ultrasonic-assisted extraction—UAE) for the formulation of oil-in-water emulsions in which pea protein concentrate served as an emulsifier. To this aim, the extracts were tested for their surface properties and their effect on the colloidal and antioxidant properties in emulsions. The extracts reduced the surface tension at the water/air interface in a dose-dependent manner, with the leaf extract obtained by UAE displaying the highest surface activity. In emulsions, the extracts increased oil droplet size and induced flocculation while being able to delay oxidation, as indicated by the induction period significantly higher compared to the control. In the last part of the work, encapsulation by spray-drying was explored on a selected leaf extract, and its release behavior in an enriched vegan mayonnaise was tested by in vitro digestion. The encapsulation influenced the release of phenolic compounds during simulated gastrointestinal digestion of the enriched vegan mayonnaise, demonstrating promising protective effects in the gastric environment and promoting a predominant release during the intestinal phase, potentially enhancing the absorption and bio-accessibility of the phenolic compounds.